THE EFFECTIVENESS OF K-W-L (KNOW- WANT TO KNOW- LEARNED) STRATEGY TO IMPROVE STUDENT’S READING SKILL STUDY - Muniroh, Lu’lu’i (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study aims to find out whether teaching reading skill by using K-W-L ( Know- Want to Know- Learned ) strategy at the first grade students of SMA Negeri 4 Kediri is effective. This study was conducted by using K-W-L ( Know- Want to Know- Learned ) strategy, particularly on text genre related to generic structure, main idea, topic, specific information, reference, moral message, inference, reference and vocabulary. Descriptive quantitative experimental with one group pre-test and post-test design was used in this study. The data collected by using multiple choices reading comprehension test, observation and questionnaire. The data gotten were statistically computed by SPSS. The result of this study showed that t-test is 12.075. It’s higher than t-table at 5% significance level. So, it can be concluded that teaching reading skill by using K-W-L ( Know- Want to Know- Learned ) strategy is effective and improve students’ reading skill. It is recommended to the students to develop their reading skill and make them interested in reading.